Microbiome Composition and Dynamics of a Reductive/Oxidative Bioelectrochemical System for Perchloroethylene Removal: Effect of the Feeding Composition - Di Franca, Maria L.; Matturro, Bruna; Crognale, Simona; Zeppilli, Marco; Dell’Armi, Edoardo; Majone, Mauro; Petrangeli Papini, Marco; Rossetti, Simona (Frontiers in Microbiology, 2022)
Chlorinated solvents still represent an environmental concern that requires sustainable and innovative bioremediation strategies. This study describes the microbiome composition of a novel bioelectrochemical system (BES) based on the sequential reductive/oxidative dechlorination for the complete perchloroethylene (PCE) removal occurring in two separated but sequential chambers. The BES has been tested under various feeding compositions (i.e., anaerobic mineral medium MM; synthetic groundwater SG; real groundwater RG) differing in the presence of sulphate, nitrate and iron (III). In addition, the main biomarkers of the dechlorination processes have been monitored in the system under various conditions. Among them, Dehalococcoides mccartyi 16S rRNA and the reductive dehalogenase genes (tceA, bvcA, vcrA) involved in the anaerobic dechlorination have been quantified. etnE or etnC genes involved in the aerobic dechlorination have also been quantified. The feeding composition affected the microbiome, in particular when the BES was fed with RG. Sulfuricurvum enriched in the reductive compartment operated with MM and SG, suggesting complex interactions within the sulfur cycle mostly including sulfur oxidation occurring at the anodic counterelectrode (MM) or coupled to nitrate reduction (SG). Moreover, the known Mycobacterium responsible for the natural attenuation of VC via aerobic degradation was found abundant in the oxidative compartment fed with RG, in line with the high VC removal observed (92±2 %). D. mccartyi was observed in all the tested conditions ranging from 8.78E+06 (with RG) to 2.35E+07 (with MM) 16S rRNA gene copies/L. tceA was found as the most abundant reductive dehalogenase gene in all the conditions explored (up to 2.46E+07 gene copies/L in MM). The microbiome dynamics and the occurrence of biomarkers of dechlorination, along with the kinetic performance of the system under various feeding conditions, suggested promising implications for the scale-up of the BES, which couples the reductive and oxidative dechlorination to ensure the complete removal of highly chlorinated ethylenes and mobile low chlorinated byproducts.